O poeta popular Leandro Gomes de Barros e a sátira ao discurso burguês-militarista no contexto da Primeira República - Marques, Francisco Claudio Alves [UNESP] (2011)
Among the popular poets from the northeastern backlands who criticized the governmental measures of the republican government, the figure of Leandro Gomes de Barros has highlighted. His satire extends to the representatives of the government in the context of the First Republic, striking politicians, bachelors, priests, colonels and oligarchs. We show here the biographical traces of the poet and a stretch from my Doctoral Thesis in which Leandro satirizes the bourgeois-militarist speech from Olavo Bilac.